Analisis Pengaruh Bank Sampah Malang (BSM) terhadap Pendapatan Masyarakat Kota Malang - Fika Fitriasari; Dewi Nurjannah (Universitas Bunda Mulia, 2016)
This study aims to determine the effect of Bank Sampah Malang (BSM) on income at the Village Community, Gading Kasri Klojen District of Malang. This is a survey research , which held data collection, data analysis and interpretation of data which aims to create a picture of the events that occurs that the time of the existing research in the area of the Village Gading Kasri. The data used in the form of primary data and secondary data, primary data were obtained from direct questioning through interviews, questionnaires and documentation of communities included in group BSM. Secondary data were obtained from BSM community groups in Gading Kasri. These data are based on analysis of financial indicators by using simple linear regression analysis. Based on data analysis, after this BSM program, there was a slight increase in their income of the people in the village Gading Kasri. It is obtained from the respondents who answered their financial condition improved slightly after the BSM program. Although the time period to earn money every month is not all, but a little community helped with the results obtained for particular needs. The results of the analysis indicated that the Savings Bank Sampah Malang (BSM) has not affect on the Income Village Community Gading Kasri, because the F-test value was smaller than F table value. This indicates that the BSM savings has not become a major source of revenue Gading Kasri Village Society. Because most people have their own primary source of income, and the Bank Sampah Malang Savings just as a side incomeKeywords: BSM (Bank Sampah Malang), Community Income, Saving.